Level of political cynicism and political efficacy among the faculty members of Leonora S. Salapantan National High School. - Calanza, Jean T.
The perception of an individual, its level of participation, reaction or response to society specifically by the political system basically has an adverse effect on government or the political system itself. The extent or level of political participation one displays depends on political stimuli he receives. And this level of participation also affects his attitude or behavior towards politically-significant objects. This researched focused on the attitude of individuals towards the political system as affected by their knowledge and its programs and policies being implemented., This study used a descriptive and relational research design. This study utilized a questionnaire prepared by the researcher. The respondents were faculty members of Leonora S. Salapantan National High School of San Miguel Iloilo. The hypotheses of the study were as follows: 1)There is a significant relationship between se, religion, years in service, educational attainment, residence, area of specialization and rank and level of political cynicism of faculty members of Leonora S. Salapantan National High School in San Miguel, Iloilo; 2.) There is a significant relationship between sex, religion and years of service, educational attainment, and residence, area of specialization and rank and level of efficacy of faculty members of Leonora S. Salapantan National High School in San Miguel, Iloilo, and; 3.) There is a significant relationship between the level of political cynicism and political efficacy of the respondents. As validity test, pre-test was conducted to 6 respondents not included in this study. Face validation was also done by someone knowledgeable in political participation, political cynicism and political efficacy. The result of the study shows that the socio-demographic characteristics of the respondents have no relationship to their level of political cynicism and level of efficacy of the respondents towards the Local Government Unit of San Miguel, Iloilo in its compliance with the Local Government Code. Based on the results, the hypotheses were therefore rejected. Moreover, it was found out that although the respondents possesses moderate to high level of political cynicism, they remain efficacious. This means that the perception and attitude of an individual towards the political system does not affect this level of political participation. This maybe due to the fact that people were vigilant enough to know if what is happening in the political arena for this event or issue might affect him, ma it be directly or indirectly.